2020
DOI: 10.21031/epod.766266
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Reliability Generalization Study of the Oxford Happiness Scale in Turkish Sample

Abstract: The purpose of this study was to analyze the meta-analytical reliability generalization of short form and long form of the Oxford Happiness Scale (OHS) for Turkish sample. In addition, how different moderator variables affect reliability coefficients was examined. A number of criteria have been set to determine the studies to be included in meta-analysis. Of 95 Cronbach's Alpha coefficients obtained from 92 studies that were selected according to criteria were included in the meta-analysis. In the data analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…As a result of the study, when the sample type variable was examined for the short form of the measurement tool, it was determined that the average 𝛼𝛼 values for studies with and without students were .75 and .77, respectively. The result of this study is similar to the result of Özdemir, Yıldırım, and Tan (2020). In addition to this, Caruso et al ( 2001), Vacha-Haase (1998), andYin andFan (2000) concluded that sample type affects the overall reliability estimation.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 87%
See 1 more Smart Citation
“…As a result of the study, when the sample type variable was examined for the short form of the measurement tool, it was determined that the average 𝛼𝛼 values for studies with and without students were .75 and .77, respectively. The result of this study is similar to the result of Özdemir, Yıldırım, and Tan (2020). In addition to this, Caruso et al ( 2001), Vacha-Haase (1998), andYin andFan (2000) concluded that sample type affects the overall reliability estimation.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 87%
“…When the results are examined, it is seen that the reliability values of the LSS used in studies whose sample does not consist of university students are higher. Özdemir, Yıldırım, and Tan (2020) examined the meta-analytic reliability generalization of the short and long form of the Oxford Happiness Scale (OHS), which measures a construct similar to the construct measured by the LSS, for the Turkish sample and included 95 Cronbach Alpha coefficients obtained from 92 studies in the meta-analysis. As a result of the study, when the sample type variable was examined for the short form of the measurement tool, it was determined that the average 𝛼𝛼 values for studies with and without students were .75 and .77, respectively.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%